APLIKASI TEPUNG CANGKANG TELUR AYAM TERHADAP PERTUMBUHAN BENIH KOPI ROBUSTA (Coffea canephora L.) PADA MEDIA GAMBUT: APLIKASI TEPUNG CANGKANG TELUR AYAM TERHADAP PERTUMBUHAN BENIH KOPI ROBUSTA (Coffea canephora L.) PADA MEDIA GAMBUT - Rosmalinda Rosmalinda; Beny Setiawan; Apriani Lita (Journal of Agro Plantation (JAP), 2022)
ABSTRACT Coffee (Coffea sp.) is one type of plantation plant that has been cultivated for a long time and has a fairly high economic value. This study aims to determine the effect of chicken egg shell flour on Robusta coffee seeds on peat media. Egg shell contains 97% calcium carbonate, the rest is phosphorus, magnesium, sodium and potassium. This study aims to determine the effect of giving chicken eggshell flour on the growth of coffee seedlings on peat media. This research was conducted from September to December 2021 at the Ketapang State Polytechnic. This research was conducted using a completely randomized design (CRD) consisting of 5 treatments. The treatments were K0: without chicken egg shell flour, K1: 6.25 gr/plant, K2: 10.0 gr/plant, K3: 13, 75 gr/Plant, K4: 17.50 gr/Plant. Each treatment was repeated 6 times, each replication consisted of 3 plant samples until there were 90 experimental units. The data that has been obtained were analyzed using Analysis Of Variance (ANOVA). Data that has a significant effect, then continued with the Duncan Multiple Range Test (DMRT) at a level of 5%. The provision of chicken eggshell flour had a significant effect on the growth of plant height, number of leaves, stem diameter, root length and dry weight of robusta coffee plants, chicken eggshell flour at a dose of 17.50 g/plant was the best dose that affected the vegetative growth of coffee plants at this parameter. plant height, stem diameter, number of leaves, root length and dry weight of robusta coffee plants. Keywords : Flour, shells, eggs, chicken, coffee.